Collaborative Governance Dalam Pengendalian Pencemaran Air Di Kota Dumai - Hastaningsih, Habsari; Adianto, Adianto; As`ari, Hasim (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2022)
The problem that arises due to increasing population growth and human activities is the contamination of water in water sources due to the waste produced by humans. The purpose of this research is to analyze collaborative governance in controlling water pollution, identify inhibiting factors and identify efforts to improve collaborative governance in controlling water pollution in Dumai City. This type of research is a qualitative research with a descriptive case study approach. The study was conducted in Dumai City, especially the waters of the Mesjid River in the Bangsal Aceh Village, Sungai Sembilan District on the grounds that the waters of the Mosque River were indicated to be in heavily polluted conditions as the results of laboratory analysis from 2017 to 2020, the results of this research are Collaborative governance in controlling water pollution in Dumai City has not run optimally